THE PROBLEMS OF TRANSLATION AND PECULIARITIES OF TECHNICAL TEXTS - Jumayeva Ilmira Yoqub qizi (Ta’lim innovatsiyasi va integratsiyasi, 2024)
ABSTRACT: Although, the sphere of translation is a wide and includes so many fields, every field has its own peculiarities and differences. Exploring these differences, the important role of culture in translation process of technical texts and its results, the similar translations, even though there are various versions in different languages and spheres - all of them are defined in this article.